AB0705 Continued effectiveness of a biosimilar adalimumab after stoppage of initial treatment in patients with ankylosing spondylitis. (15th June 2017) - Bandyopadhyay, S; Ray, A; Sarkar, RN; Dash, S; Mondal, S
Abstract : Background: Adalimumab, an anti TNF-α agent, has been proven to be safe and effective in treatment of ankylosing spondylitis (AS). A biosimilar adalimumab was approved for use by Indian regulators in 2014. It is a "fingerprint match" of the reference adalimumab in terms of purity, potency, safety and clinical efficacy. 1, 2 ln the absence of availability of adalimumab in India, this biosimilar adalimumab currently serves as an accessible, cost-effective option for treatment of AS patients. Objectives: This retrospective analysis evaluates effectiveness of biosimilar adalimumab (bADA), in terms of disease activity, safety and outcomes in real-life Indian AS patients treated for initial 24 weeks and then followed for next 24 weeks off biologic treatment. Methods: Medical records of AS patients with Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Bath Ankylosing Spondylitis Functional Index (BASFI) >4, who were prescribed bADA therapy between January to December 2015 were analysed. For patients, who stopped bADA treatment after 24 weeks, standard AS outcome-measurement scores including ESR, CRP, BASDAI, BASFI, and Health Assessment Questionnaire (HAQ) at baseline, week 24 and at week 48 were measured to evaluate ongoing efficacy, were compared using paired Student's T-test. Patients were allowed to continue methotrexate and salazopyrin as part of routine medical care. Results: During the study period, 52 AS patients were prescribed bADA 40 mg s/c; 24 of these patients, who had stopped treatment after 6 months, were considered for this analysis. Mean age for this group was 36.57±10.81 years; 10 females. At the end of 24 weeks' treatment, there were significant reductions in levels of inflammatory markers ESR, CRP, as well as in BASDAI, BASFI and HAQ scores. Eight patients continued to receive methotrexate and 8 patients sulfasalazine as concomitant medications. After week 48 (24 weeks post stoppage), BASDAI and BASFI scores did not deteriorate despite discontinuation of bADA treatment. The patients' HAQ scores were also indicative of similar trends of continuing improved health status post the therapy. Conclusions: Biosimilar adalimumab therapy was effective in treating AS patients. The disease activity and health assessment scores continued to remain stable with no worsening after the stoppage of treatment for 6 months, indicating a post-therapy effectiveness in these patients with no reported adverse event. References: Bandyopadhyay S, et al. Biosimilars. 2015;5:1–18. Jani RH et al. int J Rheum Dis. 2015 Jul 14. Disclosure of Interest: None declared